Photoredox/Cr-catalyzed enantioselective radical-polar crossover transformation via C-H functionalization - Si-Yuan Tang; Zhan-Jie Wang; Yu Ao; Ning Wang; Huan-Ming Huang (Nature Communications)
Abstract Asymmetric multicomponent reactions that aim to control multiple chiral centers with high selectivity in a single step remain an on-gonging challenge. The realm of enantioselective radical-polar crossover transformation achieved through C-H Functionalization has yet to be fully explored. Herein, we present a successful description of a photoredox/Cr-catalyzed enantioselective three-component (hetero)arylalkylation of 1,3-dienes through C-H functionalization. A diverse array of chiral homoallylic alcohols could be obtained in good to excellent yields, accompanied by outstanding enantioselectivity. The asymmetric radical-polar crossover transformation could build two chiral centers simultaneously and demonstrates broad substrate tolerance, accommodating various drug-derived aldehydes, (hetero)aromatics, and 1,3-diene derivatives. Preliminary mechanistic studies indicate the involvement of a radical intermediate, with the chiral allylic chromium species reacting with various aliphatic and aromatic aldehydes through Zimmerman–Traxler transition states enabled by dual photoredox and chiral chromium catalysis.